Identification of certain bioactive compounds with anthelmintic properties in Azadirachta indica and Clerodendrum viscosum (Asian-Australasian Journal of Bioscience and Biotechnology, 2018)
This study was undertaken to detect certain bioactive compounds with anthelmintic properties in Azadirachta indica and Clerodendrum viscosum by using high performance liquid chromatography (HPLC). From the HPLC analysis A. indica showed peak retention time which was similar to standard phenolic compounds including tannic acid (A. indica retention time 3.270 min, STD retention time 3.271 min) and pyrogallol (A. indica retention time 3.948 min, STD retention time 3.795 min). Benzoic acid (C. Viscosum retention time 6.092 min, STD retention time 6.067 min), tannic acid (C. Viscosum retention time 3.322 min, STD retention time 3.271 min) and quercetin (C. Viscosum retention time 4.967 min, STD retention time 4.222 min) was detected in leaf part of C. Viscosum. Most of these ingredients have well-known anthelmintic roles. Thus, it can be concluded that Azadirachta indica and Clerodendrum viscosum leaves contain bioactive compounds with anthelmintic properties.Asian Australas. J. Biosci. Biotechnol. 2018, 3 (2), 170-173